No associations of a set of SNPs in the Vascular Endothelial Growth Factor (VEGF) and Matrix Metalloproteinase (MMP) genes with survival of colorectal cancer patients. (23rd June 2016) - Dan, Lydia A.; Werdyani, Salem; Xu, Jingxiong; Shestopaloff, Konstantin; Hyde, Angela; Dicks, Elizabeth; Younghusband, Ban; Green, Jane; Parfrey, Patrick; Xu, Wei; Savas, Sevtap
Abstract: In this study, we aimed to investigate the associations of genetic variations within select genes functioning in angiogenesis, lymph‐angiogenesis, and metastasis pathways and the risk of outcome in colorectal cancer patients. We followed a two‐stage analysis: First, 381 polymorphisms from 30 genes (eight Vascular Endothelial Growth Factor (VEGF) and 22 Matrix Metalloproteinase [MMP] genes) were investigated in the discovery cohort ( n  = 505). Then, 16 polymorphisms with the lowest P ‐value in this analysis were investigated in a separate replication cohort ( n  = 247). Genotypes were obtained using the Illumina ® HumanOmni‐1‐Quad (discovery cohort) and Sequenom MassArray ® (replication cohort) platforms. The primary outcome measure was overall survival (OS). Kaplan–Meier, univariate and multivariable Cox regression methods were used to test the associations between genotypes and OS. Four SNPs (rs12365082, rs11225389, rs11225388, and rs2846707) had the univariate analysis P  < 0.05 in both the discovery and replication cohorts. These SNPs are in linkage disequilibrium with each other to varying extent and are located in the MMP8 and MMP27 genes. In the multivariable analysis adjusting for age, stage, and microsatellite instability status, three of these SNPs (rs12365082, rs11225389, rs11225388) were independent predictors of OS ( P  < 0.05) in the discovery cohort. However, the same analysis in the replication cohort did not yield statistically significant results. Overall, while the genetic variations in the VEGF and MMP genes are attractive candidates as prognostic markers, our study showed no evidence of associations of a large set of SNPs in these genes and overall survival of colorectal cancer patients in our study. Abstract : Angiogenesis, lymph‐angiogenesis, and metastasis are biological processes involved in tumor progression and patient outcomes. In this study, we tested the associations of 381 gene polymorphisms from these pathways with overall survival time in colorectal cancer patients. Our results suggest no evidence of independent associations of these polymorphisms with outcome in colorectal cancer.